Autotransplantation of a Mature Mandibular Third Molar to Replace Hopeless Mandibular First Molar Autotransplantation of a Mature Mandibular Third Molar to Replace Hopeless Mandibular First Molar - Samar Fatemi; Sonbol Fatemi; Maryam Boojarpoor (Mashhad University of Medical Sciences, 2013)
In this case report, a mature third mandibular molar was transplanted in the socket of a hopeless first mandibular molar of the same quadrant. A 32-year-old woman was diagnosed with strip perforation of her left first lower molar. Orthograde and retrograde treatments were unsuccessful. The tooth was extracted and replaced by the third molar of the same quadrant. Following transplantation, the tooth was splinted and the soft tissue was sutured. Removing sutures and pulp extirpation were carried out one week later simultaneously while the splint was left for one month. Prior to root canal therapy completion, calcium hydroxide therapy was considered for the tooth. Root canal treatment was completed after 3 months and the tooth was restored. Despite presence of granulation tissue in the socket of the first molar and closed apex of the wisdom tooth, the 9-months follow up revealed that the treatment was successful and no signs and symptoms were detected. In clinical examination, probing depth was normal and the radiograph indicated no pathological changes. The tooth was not tender to percussion and the absence of metal sound was indicative of no replacement resorption.